Norma decyzyjna, stare decisis i praktyka sądowa: [Decisive norm, stare decisis and judicial practice] (Studia Prawnicze / The Legal Studies, 1985)
The author considers one of the fundamental problems from the theory of law, namely the role of judicial practice in creating law. On the basis of J. Wróblewski’s definition of a procèdent he studies the problem of functioning of factual precedents in the conditions of continental law which is not based on the principle of stare desicis. Practice of Finnish law constitutes empirical material here. A characteristic feature in these systems is seeking ratio decidendi even when the interpretation has not a general character and it is only built in the factual description of the case. The trend results from the search in the continental system of rules which could be the basis of the solution. Thus, if they cannot be found in positive law, they are being looked for in judicial decisions. The author shows that similar problems also occured in Roman law and already then it became clear that stating reasons of the judgements and comparing them is impossible without a clear systematizing formula. Systematics should help the lawyer to ask relevant questions concerning factual material. The author says that modern legal systematics is partly out of date. It is built on the basis of Aristotelian point of view and creates abstract social roles rather than social relations.